Insights into the state of ISO14001 certification in both small and medium enterprises and industry best companies in India: the case of Delhi and Noida - Singh, Mitrabinda; Brueckner, Martin; Padhy, P. (Elsevier, 2014)
Despite growing interest in, and government support for, ISO14001 certification across Asia in recent years, little is known about issues surrounding the uptake and the effectiveness of environmental management systems in this region. There is a particular void of academic work in relation to ISO certification in India and the country's large number of small and medium enterprises; a field of inquiry this paper seeks to advance. Specifically, as a means of providing a basis for classification of firms for an analysis of the state of ISO14001 in India we test the adequacy of critical factors such as nature of business, size, year of establishment and internationalisation among small and medium enterprises and industry best companies. An analysis is presented of secondary data derived from the websites of a sample of ISO14001 certified firms located in the cities of Delhi and Noida. The data show that in the area of manufacturing the highest number of ISO14001 certifications can be recorded and that established small and medium enterprises with high turnover are more likely to adopt ISO14001 certification compared to low turnover firms. The findings inform the status of environmental management systems in India and have implications for government policy intended to foster ISO14001 uptake by Indian firms.